ANALISIS DAMPAK KEBERADAAN PASAR MODERN TERHADAP KEUNTUNGAN USAHA PEDAGANG PASAR TRADISIONAL (Studi Kasus di Pasar Tradisional Kecamatan Banyumanik Kota Semarang) - Damasus Ottis Widiandra; Hadi Sasana (Universitas Diponegoro, 2013)
Semarang is the capital of Central Java Province has the function as the center of government, commerce, industry, transportation, education, tourism and settlement. With these functions, Semarang has the potential to grow into a modern market businesses. The rapid development of modern markets in the Semarang city especially in Banyumanik district, become the reason of conducting this research.The purpose of this research is to analyze the effect of convenience, distance, product diversification, and price for traditional traders’ profits as a result of the emergence of modern markets.Variables used include Convenience, Distance, Product Diversification and Price. Analysis used was Double Linier Regression in SPSS program with a sample of 72 respondents, using sampling technique Proportional Random Sampling.The results of analysis show that there are significant differences in the distance and product diversification which will impact on profits for the traditional traders; on the other hand there is no significant difference for the convenience and price to business profits in the traditional market traders in district Banyumanik of Semarang.